'Dr Google' Will See You Now! A Review of Online Consumer Information about Anticoagulant and Antithrombotic Medication for Prevention of Recurrent Stroke. Issue 1 (2nd January 2019) - Gibson, Josephine M. E.; Ellis, Rebecca K.; Jones, Stephanie P.
Abstract: Stroke survivors increasingly use the internet to access health information. The aim of this study was to evaluate the quality of online information about anticoagulant and antiplatelet medication in stroke. 100 online information sources and 50 online news articles about anticoagulants and antiplatelets after stroke were accessed using Google in June-July 2016. Readability, overall quality, and language about prevention, risk, emotive terms, and shared decision-making were evaluated using SMOG and DISCERN tools. Most online information was from national health service (27/100) or charitable (24/100) sources, or from tabloid newspapers' websites (25/50). Median reading age for materials was 17–18 years. Quality scores were typically 3/5 with only 5 of 16 criteria scoring highly. Stroke risk reduction was typically described in absolute terms with little use of numerical or graphical data. Emotive language was frequently used, particularly in news articles. Shared decision-making was supported mainly by materials from charitable sources. This study has shown that online information about anticoagulant and antiplatelet medication after stroke requires high levels of literacy, and is often unreliable, poor quality and emotionally laden. People working with stroke survivors should facilitate access to accurate, unbiased and readable materials to promote shared decision making about medications.